2021
DOI: 10.3390/pharmaceutics13081241
|View full text |Cite
|
Sign up to set email alerts
|

Achyrocline satureioides (Lam.) DC (Asteraceae) Extract-Loaded Nanoemulsions as a Promising Topical Wound Healing Delivery System: In Vitro Assessments in Human Keratinocytes (HaCaT) and HET-CAM Irritant Potential

Abstract: Achyrocline satureioides (Lam.) DC Asteraceae extracts (ASEs) have been investigated for the treatment of various skin disorders. This study reports the effects of ASE-loaded nanoemulsions (NEASE) on the cellular viability, death by necrosis, and migration of immortalized human keratinocytes (HaCaT cell line), as well as the irritant potential through the hen’s egg chorioallantoic membrane test (HET-CAM). NEASE exhibited a polydispersity index above 0.12, with a droplet size of 300 nm, ζ-potential of −40 mV, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
(47 reference statements)
2
10
0
Order By: Relevance
“…Overall, the results are consistent with those observed for nanoemulsions prior to thickening with Carbopol ® Ultred. Thus, we demonstrated that under the conditions employed in this study, hydrogels containing nanoemulsions with A. satureioides extract maintained the evaluated parameters and are consistent with our previous study [13].…”
Section: Characterization Of the Formulationssupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, the results are consistent with those observed for nanoemulsions prior to thickening with Carbopol ® Ultred. Thus, we demonstrated that under the conditions employed in this study, hydrogels containing nanoemulsions with A. satureioides extract maintained the evaluated parameters and are consistent with our previous study [13].…”
Section: Characterization Of the Formulationssupporting
confidence: 91%
“…We recently demonstrated the potential of nanoemulsions containing the A. satureioides extract for topical use in wound healing. They presented promising effects on in vitro cell proliferation and keratinocyte migration, combined with an indication for the absence of cytotoxicity and non-irritating potential [13]. For topical application, the low viscosity of nanoemulsions is a concern, and the design of a semisolid formulation is an important consideration [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This plant contains quercetin, luteolin and 3-O-methylquercetin (Figure 5). 29 The results showed a significant increase in the viability of HaCaT cells on ASE-loaded nanoemulsions (NEASE) (up to 5 μg/mL of flavonoids). Preliminary tests showed that NEASE was able to increase cell migration at low flavonoid concentrations.…”
Section: Boerhavia Diffusamentioning
confidence: 99%
“…In chronic deep second degree burns infected with Pseudomonas aeruginosa , catechin-loaded nanocollagen dressings exhibited antibacterial and pro-angiogenic properties, and regeneration of skin appendages and orderly collagen tissue alignment were seen, which may be the result of selective modulation of TGF-β1 and TGF-β3 by catechins ( 146 ). One study combined flavonoids into lipid nanoemulsions, which increased the viability of keratin-forming cells and their ability to migrate to wounds, accelerating scar-free skin regeneration ( 147 ). In a rat wound model, adding isoflavone glycosides to the nanoemulsion increased keratinocyte viability up to concentrations of 0.5 μg/mL.…”
Section: Flavonoid-laden Dressings For Scar-free Regenerationmentioning
confidence: 99%